Implementation of LGBTQ+ affirming care policies in the Veterans Health Administration: preliminary findings on barriers and facilitators in the southern United States - Singh, Rajinder Sonia; Landes, Sara J.; Willging, Cathleen E.; Abraham, Traci H.; McFrederick, Pamela; Kauth, Michael R.; Shipherd, Jillian C.; Kirchner, JoAnn E. (Frontiers in Public Health, 2024)
Background In the United States Department of Veterans Affairs (VA), veterans who are lesbian, gay, bisexual, transgender, queer, and similar gender and sexual minoritized people (LGBTQ+) experience health disparities compared to cisgender, heterosexual veterans. VA’s LGBTQ+ Health Program created two healthcare policies on providing LGBTQ+ affirming care (healthcare that is inclusive, validating, and understanding of the LGBTQ+ population). The current project examines providers’ barriers and facilitators to providing LGBTQ+ affirming care and LGBTQ+ veterans’ barriers and facilitators to receiving LGBTQ+ affirming care. Methods Data collection and analysis were informed by the Consolidated Framework for Implementation Research, which was adapted to include three health equity domains. Data collection involved telephone interviews conducted with 11 VA providers and 12 LGBTQ+ veterans at one rural and one urban VA medical center, and one rural VA community clinic. Qualitative data were rapidly analyzed using template analysis, a data reduction technique. Results Providers described limited education, limited time, lack of experience with the population, and a lack of awareness of resources as barriers. Providers discussed comfort with consulting trusted peers, interest in learning more about providing LGBTQ+ affirming care, and openness and acceptance of the LGBTQ+ community as facilitators. LGBTQ+ veterans described a lack of provider awareness of their needs, concerns related to safety and discrimination, and structural discrimination as barriers. LGBTQ+ veterans described positive relationships with providers, knowledge of their own healthcare needs, and ability to advocate for their healthcare needs as facilitators. Although VA’s LGBTQ+ affirming care policies are in place, providers and veterans noted a lack of awareness regarding specific healthcare processes. Conclusion Allowing more time and capacity for education and engaging LGBTQ+ veterans in determining how to improve their healthcare may be the path forward to increase adherence to LGBTQ+ affirming care policies. Engaging patients, especially those from marginalized backgrounds, in strategies focused on the uptake of policy may be a path to improve policy implementation. It is possible that creating truly collaborative structures in which patients, staff, providers, leadership, and policymakers can work together towards policy implementation may be a useful strategy. In turn, improved policy implementation would result in increased physical and mental health for LGBTQ+ veterans.